Jawa Pos’s News Reporting about Islamic State of Iraq and Syria (ISIS) in East Java on Peace Journalism Perspective (Potret Jawa Pos tentang Islamic State of Iraq and Syria (ISIS) di Jawa Timur dalam Perspektif Jurnalisme Perdamaian) - Adibah Sayyidati (BBPSDMP KOMINFO MAKASSAR, 2018)
Clashes involving Islamic State of Iraq and Syria (ISIS) often become public debate. it took place in East Java. Mass media is very influential due unproper news of that violent conflict would be counterproductive to peace building efforts. Therefore, the principles of peace journalism should be applied. This thesis analyzes Jawa Pos’s news. The goal is to present news that give public an opportunities to consider the use of nonviolent action in conflictual situation. There are six principles of peace journalism namely: finding, considering, focusing on the intangible impact of violent conflict, and focusing more on positive. After analyzing Jawa Pos’s news, it can be concluded that this newspaper applied four out of six principles of peace journalism on reporting violent conflict involving ISIS in East Java. Unfortunately, the shortage of information about reconciliation effort by grassroot level made it difficult to conclude whether the fifth and sixth principles of peace journalism applied by this newspaper or not.Bentrokan yang melibatkan Islamic State of Iraq and Syria (ISIS) seringkali menjadi perbincangan hangat di ruang public, termasuk di Jawa Timur. Dalam hal ini, peran media sangat besar, terutama ketika berkaitan dengan konflik kekerasan karena pemberitaan yang tidak layak tentang konflik kekerasan justru kontraproduktif dengan usaha pembangunan perdamaian. Karena itu, prinsip-prinsip jurnalisme perdamaian sebaiknya diterapkan dalam penulisan beritanya. Koran yang diteliti pemberitaannya adalah Jawa Pos. Tujuannya adalah menyajikan berita-berita yang memberikan peluang kepada masyarakat untuk mempertimbangkan penggunaan upaya-upaya tanpa kekerasan saat berada pada situasi konflik. Ada enam prinsip dalam jurnalisme perdamaian, yaitu mencari, mengidentifikasi, melihat aspek kemanusiaan, fokus pada dampak nonfisik, dan memaknai perdamaian secara positif. Setelah dianalisis, ternyata Jawa Pos telah menerapkan empat prinsip pertama dalam jurnalisme perdamaian. Sayangnya keterbatasan informasi mengenai upaya membangun perdamaian positif dari kalangan akar rumput memunculkan kesulitan tersendiri untuk menganalisis penerapan prinsip kelima dan keenam.